SEAL LOUSE (ECHINOPHTHIRIDAE) AS VECTORS FOR INVASIVE AND INFECTIOUS DISEASE AGENTS OF PINNIPEDS - Mikhail Yu. Shchelkanov; Igor O. Katin; Elena G. Burukhina; Irina V. Pochinok; Egor M. Shchelkanov; Yuriy G. Volkov; Alexander M. Shestopalov; Irina V. Galkina (Юг России: экология, развитие, 2017)
The aim of the presented article is to analyze seal lice (Phthiraptera: Anoplura, Echinophthiridae) adaptation to aquatic environment – permanent parasites of pinnipeds, as well as available literature data about seal lice as pathogen vectors of their hosts. Discussion. The most noticeable feature of seal lice adaptation to aquatic environment has become their movement in the nasal passages of pinnipeds. However, this does not mean a complete rejection of ecto - in favor of endoparasitism. Seal lice preserved morphology-functional mechanisms of attachment to the fur and gained a number of features that facilitate the existence in the aquatic environment: the abdominal spiracles are tapered and have tube-like shape; head, thorax and especially the abdomen is covered with scale-like flattened setae, which stick to the air bubbles. The close ecological connection with the pinnipeds makes bloodsucking seal lice effective carriers of etiological agents of invasive and infectious diseases, e.g. microfilaria Acanthocheilonema spirocauda (Nematoda: Onchocercidae), Southern elephant seal virus (SESV) (Togaviridae, Alphavirus), Bartonella henselae (Rhizobiales: Bartonellaceae). Symbiont of Proechinophthirus fluctus described in 2016 was classified to the group of spotted fever Rocky mountain (Rickettsia ricketsii), which includes etiological agents of dangerous human diseases. Conclusion. It is necessary to include investigations of seal lice of pinnipeds into the programs of ecology-zoological and ecologyvirological monitoring of marine mammals.